It's always possible : transforming one of the largest prisons in the world - Bedi, Kiran, 1949- (Briar Hill, Vic. : Indra Publishing ; Dhaka : University Press, 1999)
With reference to Tihar Central Jail, New Delhi, India.
Includes index.
BIED
Complimentary copy from BIED
Keywords: Tihar Central Jail (New Delhi, India); Prisons -- India -- New Delhi; Prison wardens -- India -- New Delhi; Prison reformers -- India -- New Delhi; Social science